2012
DOI: 10.1063/1.4772651
|View full text |Cite
|
Sign up to set email alerts
|

The He + ${\rm H}_2^+$H2+ → HeH+ + H reaction: Ab initio studies of the potential energy surface, benchmark time-independent quantum dynamics in an extended energy range and comparison with experiments

Abstract: The He + H + 2 → HeH + + H reaction: Ab initio studies of the potential energy surface, benchmark time-independent quantum dynamics in an extended energy range and comparison with experiments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 74 publications
8
59
0
Order By: Relevance
“…This makes it a convenient tool for investigating resonance effects in a broad class of reactions, e.g., those involving ions and molecules, where recent time independent close coupling studies 67,68 have found a large number of non-zero helicity states contributing to the integral cross sections.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This makes it a convenient tool for investigating resonance effects in a broad class of reactions, e.g., those involving ions and molecules, where recent time independent close coupling studies 67,68 have found a large number of non-zero helicity states contributing to the integral cross sections.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Theoretical studies require, then, larger spatial grid sizes, making the quantum dynamical simulation computationally expensive. [1][2][3][4][5][6][7][8][9][10][11][12][13] Many of these systems possess no activation barrier in the entrance channel. As a result, a large number of partial waves is required to converge the cross sections and the J-shifting method usually does not work very well.…”
Section: Introductionmentioning
confidence: 99%
“…It is then not surprising that the structure and dynamics of, for example, RgH + 2 (Rg = He, Ne, Ar) systems, have been the subject of a large number of both theoretical and experimental studies: ab initio electronic structure, ro-vibrational spectra, reaction cross sections, and rate constants have been calculated before. 4,[6][7][8][15][16][17][18][19][20][21][22][23][24][25][26] Complexes containing two rare gas atoms and a proton are also well studied. 12,[27][28][29][30][31][32][33][34][35][36] Both RgH + 2 a) t.gonzalez.lezana@csic.es b) adi07@iitg.ernet.in and [RgHRg/Rg ] + cases are found to display a global potential energy minimum at the collinear configuration.…”
Section: Introductionmentioning
confidence: 99%
“…For the nuclear motion computations presented in this paper, the PES of H 2 He + was taken from Ref. 63 In the full-dimensional GENIUSH vibration-only boundstate computations, we use 40 and 200 scaled Laguerre-DVR points along the r and R coordinates in the range of [1.0, 5.0] and [0.5, 40.0] bohrs, respectively. On the angular coordinate, we use 40 unscaled Legendre-DVR points in the interval of (0.0, 180.0) • .…”
Section: A Computational Detailsmentioning
confidence: 99%